Implementation of the Language Experience Approach to Improve Students' Writing Skills at SD Negeri Siem - Eva Niatul Husna; Nurhasanah (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to improve the writing skills of grade II students of SD Negeri Siem through the application of the Language Experience Approach (LEA) method. The background of this research is the low writing ability of students, as can be seen from the pre-cycle results that are still below the Minimum Completeness Criteria (KKM) set. This research uses the Classroom Action Research (PTK) approach which is carried out in two cycles, each through the stages of planning, implementation, observation, and reflection. The research subjects amounted to 21 students, consisting of 11 males and 10 females. Research data was collected through writing learning outcome tests, observation of student activities, and documentation during the learning process. The results showed a significant improvement in writing skills after the application of the LEA method. In the pre-cycle, most students have not reached KKM. After the implementation of the first cycle, students' writing skills began to improve, although there were still some who did not meet the criteria. In cycle II, almost all students managed to achieve KKM with a clear improvement in terms of sentence structure, vocabulary choice, and courage to pour ideas in written form. Thus, the application of the LEA method has proven to be effective in improving the writing skills of grade II students of SD Negeri Siem.